Predictability of a drastic reduction in the Arctic sea ice with climate model MIROC - Jun, Ono; Hiroaki, Tatebe; Yoshiki, Komuro (2017)
第8回極域科学シンポジウム/個別セッション：[OM] 極域気水圏 12月6日（水）国立極地研究所 2階大会議室 The Eighth Symposium on Polar Science/Ordinary sessions: [OM] Polar Meteorology and Glaciology Wed. 6 Dec./2F Auditorium, National Institute of Polar Research conference object